Controversy in a time of change : An analysis of gaming discourse on Reddit - Enberg, Verneri (My University, 2025)
This thesis explores the discourse surrounding videogames on the online forum Reddit r/gaming. The aim of the thesis was to analyse how video game discourse reflects the views, interests and values of those who participate in it. The material was text data from two of the most commented posts from the year 2024, which were then formatted into corpora. The corpora were edited to remove personal identifiers and duplicates. The purpose of the research was to study video game discourse and its prevalent themes. Results of the research were that personal values and ideologies are prevalent in video game discourse. Another theme was the discourse surrounding what makes a game good or successful. The divide between those in the hobby and those in the industry was also a point of conflict.
Keywords: Gaming Discourse, Corpus-Based Linguistics, Astro Bot, Concord